Simplifying Square Roots Homework Help

We’ve answered 396,870 questions. We can answer yours, too.

Ask Your Question

eNotes Homework Help is a way for educators to help students understand their school work. Our experts are here to answer your toughest academic questions! Once it’s posted to our site, your question could help thousands of other students.

in Simplifying Square Roots

  • Math
    Firstly note that `sqrt(12) = sqrt(3 times 4) = sqrt(3) times sqrt(4) = 2sqrt(3)` So we then have that `2sqrt(3) + sqrt(12) = 2sqrt(3) + 2sqrt(3)` This simplifies to `2 times 2sqrt(3) = 4sqrt(3)...

    Asked by sighcopath on via web

    1 educator answer.